القابليات التنظيمية وأثرها في السلوك الإبداعي للعاملين دراسة حالة -شركة موبيليس الجهوية عنابة- - إيمان عمروني; إيمان شلبي (My University, 2021)
The study aims to know the impact of organizational capabilities through the two dimensions (organizational learning and knowledge management) on the reative behavior of employees, Where the study aimed to answer the following problem: What is the impact of the dimensions of organizational capabilities on he creative behavior of employees in the Mobilis Regional Telecom Company in Annaba? The main hypothesis included the following, “there is a significant ffect of organizational capabilities on the creative behavior of employees in Mobilis”. In order to answer the main question and achieve the objectives of the tudy, the descriptive approach and the case study approach were followed, through the use of the questionnaire in order to obtain and process field data in the pss program. Inferential statistics were also used to test the hypotheses, and the questionnaire tools. What produced a set of results that approved a set of conclusions, the most important of which are: - The formation of organizational capabilities is related to the skill of the creative person of the organization with a high level of appropriate decision-making that distributes the organizational capabilities of the organization and achieves its goals; - There is a significant effect of organizational capabilities on the creative behavior of employees in the Mobilis Telecommunications Company. The study also reached a set of recommendations, the most important of which are: - The culture of teamwork must be relied upon in carrying out tasks because it affects the process of organizational capabilities, which is a collective process in hich the efforts of all employees are integrated to enhance learning opportunities and disseminate them throughout the company; - It is necessary to generalize training to improve the efficiency of workers and raise their capabilities in all fields, as well as to show their creativity. ............................................ تهدف الدراسة إلى معرفة أثر القابليات التنظيمية من خلال بعديها )التعلم التنظيمي وإدارة المعرفة( على السلوك الإبداعي للعاملين في الشركة الجهوية للإتصالات موبيليس، حيث عمدت الدراسة الإجابة على الإشكالية التالية: مامدى تأثير أبعاد القابليات التنظيمية في السلوك الإبداعي للعاملين في الشركة الجهوية للإتصالات موبيليس بعنابة؟ وتضمنت الفرضية الرئيسية الآتية: "يوجد تأثير معنوي للقابليات التنظيمية على السلوك الإبداعي للعاملين في شركة الجهوية للإتصالات موبيليس". وللإجابة على التسا ؤل الرئيسي وتحقيق أهداف الدراسة تم إتباع المنهج الوصفي ومنهج دراسة الحالة، من خلال الإستعانة بالإستبيان من أجل الحصول على البيانات الميدانية ومعالجتها في برنامج كما تم اللجوء إلى الإحصاء الإستدلالي لإختبار الفرضيات، وعلى أدوات الإستبيان. ما أفرز مجموعة من النتائج التي أقرت مجموعة ،Spss من الإستنتاجات أهمها : - إن تشكيل القابليات التنظيمية مرتبط بمهارة الشخص المبدع للمنظمة ذات مستوى عال لصنع القرار المناسب الذي يوزع القدرات التنظيمية للمنظمة ويحقق أهدافها؛ - يوجد تأثير معنوي للقابليات التنظيمية على السلوك الإبداعي للعاملين في شركة الجهوية للإتصالات موبيليس. كما قدمت الدراسة مجموعة من التوصيات أهمها: يجب الإعتماد على ثقافة العمل الجماعي في تنفيذ المهام لتأثيره على عملية القابليات التنظيمية والتي تعتبر عملية جماعية تتكامل  فيها جهود جميع العاملين من أجل تعزيز فرص التعلم وتعميمها في جميع أرجاء الشركة؛ من الضروري تعميم التدريب لتحسين كفاءة العاملين ورفع من قدراتهم في كافة المجالات، وأيضا لإظهار قدراتهم الإبداعية.